2012
DOI: 10.1007/s00134-012-2658-1
|View full text |Cite
|
Sign up to set email alerts
|

How to implement monitoring tools for sedation, pain and delirium in the intensive care unit: an experimental cohort study

Abstract: A modified extended training strategy for ICU monitoring tools (sedation, pain, delirium) leads to higher intermediate and long-term implementation rates and is associated with improved patient outcome. However, these findings may have been biased by unmeasured confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 25 publications
4
43
0
7
Order By: Relevance
“…One study, for example, that explored the implementation of sedation, pain and delirium tools found that extended repetitive training led to higher implementation rates than one time training alone. 28 Another possible explanation was that the research team did almost all of the education and monitoring of outcomes. If these changes were initiated and implemented purely by the clinical staff, buy-in may have improved due to an increased sense of ownership.…”
Section: Discussionmentioning
confidence: 99%
“…One study, for example, that explored the implementation of sedation, pain and delirium tools found that extended repetitive training led to higher implementation rates than one time training alone. 28 Another possible explanation was that the research team did almost all of the education and monitoring of outcomes. If these changes were initiated and implemented purely by the clinical staff, buy-in may have improved due to an increased sense of ownership.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a point prevalence analysis within an international survey showed that 73% of observed patients were not monitored with a validated delirium score [18]. Despite the low implementation rates, delirium monitoring implementation has been shown to be feasible [25,28].…”
Section: Discussionmentioning
confidence: 92%
“…The training method used, included on-the-job-training periods provided by a multi-professional team of nurses and physicians [25].…”
Section: Main Predictor Variablementioning
confidence: 99%
“…In addition, as part of the implementation of the algorithm, the principal investigator and the resource person reminded the nurses to use the algorithm, because feedback strategies were shown to improve adherence in other studies. 20,23,24 Radtke and colleagues 26 found that sustained documentation rates for sedation, pain, and delirium scores increased significantly when they used an expanded training program (i.e., resource group, lectures, movie, handouts, one to one instructions over three cycles) compared to a traditional training program (i.e., over one cycle). In the current study, a traditional training approach was used.…”
Section: Nurses' Adherence With the Algorithmmentioning
confidence: 98%